2006
DOI: 10.1093/nar/gkl550
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model for replication protein A (RPA) function in DNA processing pathways

Abstract: Processing of DNA in replication, repair and recombination pathways in cells of all organisms requires the participation of at least one major single-stranded DNA (ssDNA)-binding protein. This protein protects ssDNA from nucleolytic damage, prevents hairpin formation and blocks DNA reannealing until the processing pathway is successfully completed. Many ssDNA-binding proteins interact physically and functionally with a variety of other DNA processing proteins. These interactions are thought to temporally order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
668
5
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(694 citation statements)
references
References 121 publications
18
668
5
3
Order By: Relevance
“…We show that indeed as expected, Killin always adopts a mutually exclusive punctuated nuclear expression pattern with the 2 important accessory proteins in DNA replication. [19][20][21][22][23] Furthermore, we also notice that in non-S-phase cells, RFP-Killin congregates in the nucleolus where rRNA transcription is known to be most active. 24 We provide evidence that throughout the cell cycle, RFPKillin is tightly associated with the nucleic acids.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…We show that indeed as expected, Killin always adopts a mutually exclusive punctuated nuclear expression pattern with the 2 important accessory proteins in DNA replication. [19][20][21][22][23] Furthermore, we also notice that in non-S-phase cells, RFP-Killin congregates in the nucleolus where rRNA transcription is known to be most active. 24 We provide evidence that throughout the cell cycle, RFPKillin is tightly associated with the nucleic acids.…”
Section: Introductionmentioning
confidence: 62%
“…The mutually exclusive patterns of DNA replication foci labeled by BrdU with RFP-Killin foci strongly support that Killin inhibits DNA replication during the S-phase. Given the fact that the K d of Killin to ssDNA template is very similar to that of RPA, 17,21 both of which are in the sub mM range, it is possible that Killin could interfere with DNA replication by competitively inhibit RPA binding to ssDNA templates during the onset of DNA replication. To this end, we conducted confocal fluorescent microscopy by looking at the precise RFP-Killin expression pattern in relationship with DNA replication foci marked by immunofluorescent staining of endogenous RPA.…”
Section: Resultsmentioning
confidence: 99%
“…Other DNA repair proteins and factors that bind and/or repair single-stranded DNA include the human and vaccinia virus uracil-DNA glycosylases (49,50), human DNA glycosylases NEIL1 and NEIL2 (51), human apurinic/apyrimidinic endonuclease (APE1) (52), and Xeroderma pigmentosum group A correcting protein (XP-A) (53,54). In addition, XP-A is associated with the replication protein A single strand-binding protein (55,56), whereas components of the transcription-coupled nucleotide excision repair complex are associated with XP-B and XP-D DNA helicases (57). It seems reasonable to expect that these interaction partners increase the availability of single-stranded templates for repair.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of RPA with those proteins are critical in this process (Wold, 1997;Iftode et al, 1999). A great deal of protein dynamics research has indicated that the interactions between RPA and other DNA-metabolism proteins are choreographed on the ssDNA to recruit the required protein present at the proper time (Fanning et al, 2006). Human, animals, and fungi have single copy for each subunit of RPA (http://www.ncbi.nlm.nih.gov/ sutils/genom_table.cgi).…”
mentioning
confidence: 99%